PENGARUH PEMBERIAN PUPUK BOKASHI FESES SAPI SUMBA ONGOLE TERHADAP NILAI NUTRISI SESBANIA GRANDIFLORA - Yosafat Ndamuyilu; Marselinus Hambakodu (JURNAL PETERNAKAN SABANA, 2022)
The aims of the experiment was to determine the effect of bokashi fertilizer Sumba Ongole cattle Sumba Ongole cattle on the nutritional value of the Sesbania grandiflora. This experiment used a completely randomized design (CRD) with 5 treatments with 4 replications consisting of P0: without bokashi fertilizer Sumba Ongole cattle/planting hole, P1: bokashi fertilizer Sumba Ongole cattle 200 grams/planting hole, P2: bokashi fertilizer Sumba Ongole cattle 500 grams/planting hole, P3: bokashi fertilizer Sumba Ongole cattle 800 grams/planting hole, and P4: bokashi fertilizer Sumba Ongole cattle 1000 grams/planting hole. The variables observed in this experiment consisted of crude protein and crude fiber. The results showed that the bokshi fertilizer Sumba Ongole cattle feces had not significant effect (P<0.05) on crude protein and crude fiber. Conclusion, giving bokashi fertilizer Sumba Ongole cattle up to 1.000 grams had nutritional value same.